THE IMPACT OF PERFORMANCE IN PROJECT MANAGEMENT TO MITIGATE DELAYS IN IT PROJECT - Husin Husin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
A project delay is typically becoming a common cause in IT Projects. As one of Indonesia’s biggest palm oil companies, a total of delayed projects are ten projects (71%), and the rest of the four projects (29%) have been completed on time from 2018 until 2020. Project Management Body of Knowledge (PMBOK) 6th edition used as one of the project management approaches. The main objective of this study is to explore the impact of PMBOK on the IT project that specifically standardizes the Windows Operating System in the company. The project management proposed model includes communication between stakeholders, scope management, schedule plan, risk response plan, and project documentation. The model improves solving the delay in the project schedule and receives a very positive response from the individuals involved. The results indicate that the application of PMBOK is a way to align with the project schedule performance.